Modeling and Simulation of Grid Connected PV Generation System Using Matlab/Simulink - Omar Mohammed Benaissa; Samir Hadjeri; Sid Ahmed Zidi (Institute of Advanced Engineering and Science, 2017)
This paper describes the Grid connected solar photovoltaique system using DC-DC boost converter and the DC/AC inverter (VSC) to supplies electric power to the utility grid. The model contains a representation of the main components of the system that are two solar arrays of 100 kW, boost converter and the grid side inverter. The paper starts with a system description, in this part we have given a definition and a short overview of every component used in this system and they are taken separately. The PV cell model is easy, accurate, and takes external temperature and solar radiation into consideration. It also proposes a maximum power point tracking (MPPT) algorithm. The algorithm incorporated in a DC/DC converter is used to track the maximum power of PV cell. Finally, the DC/AC inverter (VSC) of three- level is used to regulate the ouput voltage of DC/DC converter and connects the PV cell to the grid. Simulation results show how a solar radiation’s change can affect the power output of any PV system, also they show the control performance and dynamic behavior of the grid connected photovoltaic system.